2018
DOI: 10.1093/jas/skx006
|View full text |Cite
|
Sign up to set email alerts
|

Reaction norm for yearling weight in beef cattle using single-step genomic evaluation1

Abstract: When the environment on which the animals are raised is very diverse, selecting the best sires for different environments may require the use of models that account for genotype by environment interaction (G × E). The main objective of this study was to evaluate the existence of G × E for yearling weight (YW) in Nellore cattle using reaction norm models with only pedigree and pedigree combined with genomic relationships. Additionally, genomic regions associated with each environment gradient were identified. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 23 publications
8
20
0
3
Order By: Relevance
“…The (G)EBV predictive abilities obtained using RNM_H were moderate (from 0.32 to 0.51 for SC and from 0.28 to 0.43 for HP). Our results are similar to those found by Oliveira et al () using a model including G×E interaction for Nellore body weight. The authors reported an increase in the predictive ability of 7.9% using RNM_H instead of RNM_A.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The (G)EBV predictive abilities obtained using RNM_H were moderate (from 0.32 to 0.51 for SC and from 0.28 to 0.43 for HP). Our results are similar to those found by Oliveira et al () using a model including G×E interaction for Nellore body weight. The authors reported an increase in the predictive ability of 7.9% using RNM_H instead of RNM_A.…”
Section: Resultssupporting
confidence: 92%
“…For SC, the genetic correlations estimated using the H or A matrix were similar (Fig. ), as also found by Mota et al () and Oliveira et al () using genomic information in the reaction norm for beef cattle. However, for HP, larger differences were observed in genetic correlation estimates when using the H matrix, with values ranging from 0.30 to 0.98, instead of 0.60–0.98 with the A matrix.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Nas análises, foram obtidas correlações genéticas estimadas entre ambientes extremos de 0,33 em fêmeas e 0,40 em machos. Tais valores confirmam a significância da IGA, mostrando a importância do uso de modelos de norma de reação na avaliação de rebanhos bovinos da raça Nelore, em concordância com outros resultados da literatura (PEGOLO et al, 2011;DE ARAÚJO NETO et al, 2018). …”
Section: Methodsunclassified
“…Na bovinocultura de corte, vários trabalhos já foram apresentados, discutindo a existência de interação genótipo-ambiente (IGA) nas populações em seleção das diferentes raças. O Brasil, sendo um país com grande extensão territorial, possui uma gama de sistemas de produção muito diversificada, tornando-se um local de interesse para estudos de IGA por meio dos modelos de NRAs, conforme descrito por Ferreira et al (2014), Lemos et al (2015); Hay & Roberts (2018), Chiaia et al (2015), Oliveira et al (2018) (2011) consideraram a possibilidade da seleção nas características de crescimento utilizando como critério de seleção os coeficientes preditos das NRAs, que tendem a ser transmitidos para as proles, permitindo a seleção de indivíduos com robustez ambiental, ou seja, com baixa sensibilidade às mudanças ambientais. O maior desafio associado a tal seleção consiste na padronização dos coeficientes das NRAs num índice que permita a diferenciação dos animais robustos e de baixa produção dos animais robustos e com alta produção, equilibrando o progresso de seleção para ganho de peso com a estabilidade genética.…”
Section: Introductionunclassified